Pattern of Ear Diseases in Surgical Pathology (Medical Forum Monthly, 2024)
Objective: The purpose of this study is, firstly, to find the pattern of ear diseases in the community, as no such pattern study is currently available. Secondly, to impart awareness regarding microscopic appearances of the common ear diseases encountered in this pattern study.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Surgical Pathology archives of the Laboratory of Charsada Teaching Hospital affiliated with Jinnah Medical College Peshawar from 2010 to 2015.Materials and Methods: In this study, all the cases of ear diseases from surgical pathology archives of the laboratory of Charsada Teaching Hospital were retrieved. All the slides and the diagnoses for the retrieved cases were reviewed by the histopathologist and the final diagnoses were recorded; the disease pattern was determined, keeping in view the number of cases for each diagnostic category and the patient’s age.Results: The review of these cases between 2010 and 2015 showed that most of the biopsy specimens were from external ear while few were from the middle ear. The first five commonest conditions constituted almost two thirds of the total number of cases. The congenital anomalies and juvenile xanthogranulomas were most common in the first decade of life. Benign and malignant tumors were uncommon and seen mostly after the third decade of life.Conclusions: Congenital anomalies and inflammation associated diseases are common in the first three decades of life, whereas benign and malignant neoplasms are more common after the third decade of life.